Lombok Living Strategy After The Lombok Earthquake - Hemi Wulan Martatiwi; Nurhadi Nurhadi; Chatarina Muryani (Universitas Sebelas Maret, 2020)
This study aims to determine the form of household livelihood strategies found in Kayangan District after the earthquake. This qualitative research uses the case study method by sampling using purposive sampling. The sample used in this study were 60 households. Data collection techniques in this study used triangulation. Triangulation used in this research is by using source triangulation. In addition, other data collection techniques are in the form of observation, deep interview, and documentation. Analysis of the data used in this study is a qualitative analysis using the Miles and Huberman models. Activities carried out in the analysis are in the form of scoring data, reduction, data display, and conclusion drawing / verification. The results of the study concluded that: Household livelihood strategies used by the community in Kayangan District include intensification and exensification, as well as diversification.